2017
DOI: 10.3892/mmr.2017.7651
|View full text |Cite
|
Sign up to set email alerts
|

Bufalin induced apoptosis in SCC-4 human tongue cancer cells by decreasing Bcl-2 and increasing Bax expression via the mitochondria-dependent pathway

Abstract: The aim of the present study was to investigate the cytotoxic effects of bufalin on SCC-4 human tongue cancer cells. Cell morphological changes and viability were examined using phase contrast microscopy and flow cytometry, respectively. The results indicated that bufalin induced morphological changes and reduced total viable cells. Apoptotic cell death was analyzed by DAPI staining and DNA gel electrophoresis; the results revealed that bufalin induced cell apoptosis. Levels of reactive oxygen species (ROS), C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…First, in the mitochondrial pathway, the Bcl-2 family of proteins exerts a major role in tumorigenesis and tumor maintenance. a previous study revealed that bufadienolides may mediate apoptosis through downregulation of Bcl-2 and/or upregulation of Bax in cancer cells (24,25). in the present study, bufadienolides were identified to induce the apoptosis of a-375 cells, upregulate the expression of Bax and p53, and downregulate Bcl-2 expression.…”
Section: Discussionsupporting
confidence: 63%
“…First, in the mitochondrial pathway, the Bcl-2 family of proteins exerts a major role in tumorigenesis and tumor maintenance. a previous study revealed that bufadienolides may mediate apoptosis through downregulation of Bcl-2 and/or upregulation of Bax in cancer cells (24,25). in the present study, bufadienolides were identified to induce the apoptosis of a-375 cells, upregulate the expression of Bax and p53, and downregulate Bcl-2 expression.…”
Section: Discussionsupporting
confidence: 63%
“…Bufalin has biological activities including inducing cancer cell apoptosis (11)(12)(13)(14)(15)(16)(17) and DNA damage in NCI-H460 human lung cancer cells (18). Recently, we also found that bufalin significantly inhibits cell adhesion, migration and invasion of gefitinib-resistant NCI-H460 cells (19) and induced apoptosis of U-2 OS human osteosarcoma cells (20) and SCC 4 human tongue cancer cells (21).…”
mentioning
confidence: 94%
“…For example, paclitaxel suppresses cell proliferation and induces apoptosis by increasing ROS generation in canine mammary gland tumor cells [ 45 ]. Bufalin has also been shown to induce apoptosis via reduction in ROS production in tongue cancer cells [ 46 ]. Our results showed that DIV exhibits an antitumor effect by increasing ROS generation in SCC2095 cells, and this inhibition can partially be rescued by pretreatment with antioxidants.…”
Section: Discussionmentioning
confidence: 99%